For Doubling Farmers’ Income... Exploring potential of arid horticulture - Saroj, P L (Indian Horticulture, 2019)
Traditional farming in arid and semi-arid regions is a risky proposition and production cost is also rising as compared to productivity gain, thereby eroding profit margins. It is, therefore, essential to exploit the potential of non-traditional areas with appropriate strategy and adoption of new technologies by lowering production costs, improving productivity, enhancing quality of the produce and reducing the post-harvest losses. In this context, market-driven diversification in a global perspective has become the new paradigm shift. Specialty commodities such as off-season varieties and production systems, new crops and novel varieties coupled with good management practices should be identified to capture new opportunities. Horti-business centres equipped with facilities like cold storage, processing units, packaging units, quality control facilities, financial support system, insurance facilities, etc. will catalyse better profit margin at producer level. Value-addition in horticultural produce offers good scope in domestic as well as export markets. Farmers’ organizations, prospective entrepreneurs, cooperatives, and self-help groups need to be encouraged for better income of farmers. The production system models coupled with ancillary enterprises will be of immense use for doubling income of farmers in arid and semiarid regions of the country, says Professor P L Saroj, Director, CIAH, Bikaner.